Digital platform ecosystem for insurance investment industry in Malaysia: a possible conceptual solution - Tambi, Muhamad Rezan; Ahmad Dahlan, Abdul Rahman (Kulliyyah of Information & Communication Technology, International Islamic University Malaysia, 2023)
This paper discusses the direction of a possible conceptual Digital Platform Ecosystem in Malaysia, specifically with regards to the Insurance Investment Industry and it is a response to the current situation that clearly opens the door to high risk of losses just because the system is rigid and inconvenient to the customers. In addition, the existing system is weak and has become one of the causes that burdens the customers because they will encounter errors so often while using the system. The system also triggers challenges in the governance between brokers, customers, and reinsurers, and will result in the loss of contributors. Therefore, a lightweight and easy-to-manage digital platform should be introduced for the insurance investment industry in Malaysia in order to deal with the constant errors encountered by customers and for the agents to become more user friendly and relevant, as well as secure. Therefore, this paper identifies the challenges and proposes the possible conceptual Insurance Digital Platform Ecosystem incorporating Integrated Enterprise Risk Management (IERM) to reduce the impact of the high risks identified, including the risk of financial losses caused by clients’ frustrations.